The quarry - Iain Banks (RedHook Books/Orbit,., 2013)
Kit doesn't know who his mother is. What he does know, however, is that his father, Guy, is dying of cancer. Feeling his death is imminent, Guy gathers around him his oldest friends - or at least the friends with the most to lose by his death. Paul - the rising star in the Labour party who dreads the day a tape they all made at university might come to light; Alison and Robbie, corporate bunnies whose relationship Read more...